Cultural Concept in Furniture Design : Perceptions, Issues and Challenges - Faridah, Sahari; Musdi, Shanat (2019)
Sarawak Borneo has been long known for diverse culture and multi-ethnics which reflected in its arts and crafts. Pua Kumbu and Orang Ulu motifs are among the famous visual art which can be seen on many products of textile, furniture and painting. The purpose of this paper is to identify the perception, issues and challenges of cultural concept embedded in furniture design from the perspective of manufacturers and designers. In-depth interview, survey and observation are the three qualitative research methods applied in this study during MIFF 2018 and MIFF 2019. Finding shows that each group: manufacturers and designers have their own views and strategies, looking at different aspects on how to interpret cultural element in their furniture design, deterred by their interests and global market needs.